2021
DOI: 10.1152/ajpcell.00017.2020
|View full text |Cite
|
Sign up to set email alerts
|

Preventive and therapeutic effect of anti-IL-17 in an experimental model of elastase-induced lung injury in C57Bl6 mice

Abstract: COPD is an important health care issue, and IL-17 can modulate inflammatory responses. We evaluated preventive and therapeutic effect of anti interleukin (IL)-17 in a model of lung injury induced by elastase, using 32 male C57Bl6 mice, divided into 4 groups: SAL, ELASTASE CONTROL (EC), ELASTASE + PREVENTIVE ANTI IL-17 (EP), and ELASTASE + THERAPEUTIC ANTI IL-17 (ET). On 29th day, animals were anesthetized with thiopental, tracheotomized and placed on a ventilator to evaluate lung mechanical, exhaled nitric oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 52 publications
0
12
0
1
Order By: Relevance
“…NF-kappaB plays a crucial role in oxidative stress, as excessive activation perpetuates the production of inflammatory mediators in severe asthma and may exacerbate COPD, given its association with TNF-α, IL-8, and other inflammatory cells. Notably, the expression of iNOS and cytokines related to the Th2 and Th17 profiles relies on NF-kappaB transcription ( Fukusaki, 2019 ). In our study, the experimental groups (ACO, ELA, and OVA) exhibited elevated NF-kappaB values, and the treatments were effective in reducing these values in the ACO group.…”
Section: Discussionmentioning
confidence: 99%
“…NF-kappaB plays a crucial role in oxidative stress, as excessive activation perpetuates the production of inflammatory mediators in severe asthma and may exacerbate COPD, given its association with TNF-α, IL-8, and other inflammatory cells. Notably, the expression of iNOS and cytokines related to the Th2 and Th17 profiles relies on NF-kappaB transcription ( Fukusaki, 2019 ). In our study, the experimental groups (ACO, ELA, and OVA) exhibited elevated NF-kappaB values, and the treatments were effective in reducing these values in the ACO group.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in models of elastase-induced lung damage. Elastase-induced inflammation and loss of lung structure were reduced in IL-17A-deficient mice as well as in mice treated with therapeutic anti-IL-17A antibodies [ 104 , 105 , 106 ]. Moreover, IL-17A deficiency resulted in a decreased apoptosis of alveolar type-II cells in mice exposed to CS for 4 weeks [ 107 ] and an attenuated lymphoid neogenesis in mice exposed to CS for 24 weeks [ 96 ].…”
Section: Copdmentioning
confidence: 99%
“…More recently, the efficiency of treatment with anti-IL-17 has been demonstrated to improve the inflammation observed in asthma (76,77), asthma exacerbated by LPS (78,79) and LPSinduced lung injury (80). In an elastase-induced model of emphysema, it was also demonstrated that both preventive and therapeutic treatment with anti-IL17 improved the evaluated inflammatory parameters in mice, including specific markers for the Th17 response (81).…”
Section: Treatments Targeting Th17/treg Cells In Copd and In Vitro Studiesmentioning
confidence: 99%